Improving the conjugated linoleic acid content and the sensorial characteristics of Argentinean semi-hard goat cheeses by adding cultures of native lactic acid bacteria - Taboada, Natalia (Array, 2019)
In this study the physicochemical, microbiological, and fatty acid compositions together with the specific esterase activities of semi-hard goat cheeses made from native strains as starter and adjunct cultures were evaluated and compared against those of manufactured using commercial culture cheeses. The physicochemical composition was similar among cheeses, while the lactic acid bacteria were the predominant microbiota in all samples. The highest specific esterase activities were detected in cheeses with native strains. The fatty acid profile was significantly affected by native strains during the ripening time (60 days) since the conjugated linoleic acid (CLA) level increased from 0.60 to 1.03 g 100 g-1 of fatty acids, whereas cheeses with commercial starter showed a CLA content of about 0.60 g of fatty acids. In cheeses with native strains, it was detected the highest desirable fatty acids, Δ9-desaturase and CLA desaturase indexes and the lowest atherogenicity index. The native strains inoculated as starter and adjunct cultures, grew conveniently in the cheese, developed their full potential as reflected by the profile of the metabolites released during ripening and in the global sensory perception of cheeses, and contributed thus to the development of a healthier food.